Kontribusi PAD, Dana Perimbangan, Belanja Daerah terhadap Kesejahteraan Masyarakat di Jawa Tengah - Ari Nurul Fatimah; Nuwun Priyono (JAAF (Journal of Applied Accounting and Finance), 2020)
The system of change from centralized to decentralized puts new hope for the majority of the Indonesian people. With decentralized government management or delegating authority to local governments, government management authority will be distributed from the center to the regions. The aim of this study is to examine and prove whether the income received by the government and the balance and regional expenditure funds have an effect on the welfare of the community in regencies / cities in Central Java Province. The study uses a data panel because it will examine several objects from several specific time periods (2016-2018). The data used is the entire population of districts and cities in Central Java, namely 29 districts and 6 cities. The APBD realization report data is taken from the Directorate General of Fiscal Balance and from the Central Bureau of Statistics of the Republic of Indonesia. The hypothesis will be tested using a panel data multiple regression analysis model. The results of this study, namely PAD, DAU, and the ratio of GDP to expenditure have a positive and significant impact on the welfare of the community.